Preferensi Generasi Milenial dalam Menggunakan QRIS sebagai Alat Pembayaran Digital - Mitra Sami Gultom; Huda Salsabila; Andi Amri (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
The understanding of the millennial generation in using and utilizing QRIS is still low, even though Bank Indonesia and OJK have supported the implementation of QRIS in finance. This study aims to determine the preferences of Indonesian Islamic Bank customers, especially the Millennial Generation in Using Digital Payment Instruments, namely QRIS in DKI Jakarta. The type of research used is a quantitative method with the population is the millennial generation who live in the province of DKI Jakarta. The sample obtained was 100 respondents using purposive sampling technique. The data analysis technique used is multiple linear regression with the help of SPSS software. The findings obtained are partially usefulness perception and trust perception have a positive and significant effect on preferences in using QRIS. Meanwhile, the perceived convenience and risk perception variables have a negative and insignificant effect on customer preferences. Simultaneously, these factors have an influence on the preferences of Indonesian Islamic Bank customers.